Yeast race effect on the quality of base and young sparkling wines - Alexander S. Makarov (Kemerovo State University, 2021)
Introduction. A disadvantage of the ancestral method (la méthode ancestrale), which is widely used in the production of sparkling wine, is that it is difficult to control fermentation. We aimed to identify the optimal yeast race for obtaining high-quality young sparkling wines with varietal aroma without yeast tones. Study objects and methods. Our study objects were base and young sparkling wines from Cabernet-Sauvignon prepared on various yeast races. Organic acids, sugars, and ethanol contents were determined by high performance liquid chromatography. Phenolic and coloring substances were measured by colorimetric method. Foaming properties were determined by air barbotage of a wine sample in a measuring cylinder; sparkling properties, by measuring the CO2 desorption rate; CO2 content, by volumetric method; viscosity, with a viscometer. Sensory evaluation was carried out according to standard methods. Results and discussion. The wines produced on the Odesskiy Chernyi-SD13 yeast race received the highest tasting scores of 7.82 and 9.05 points for base wine and young sparkling wines, respectively. They contained larger amounts of phenolic substances (1103 mg/dm3) and coloring agents (275 mg/dm3) and had higher color intensity (1.614). The panelists rated them highly on their complex varietal aroma and harmonious, velvety flavor, as well as their foaming and sparkling properties. This yeast race ensured intensive fermentation of sugars and a great amount of bound CO2 (up to 24.93%). Conclusion. The Odesskiy Chernyi-SD13 yeast race is optimal for making base and young sparkling wines by the bottle method. This technology can be used to produce high-quality sparkling wines in the crop year by large and small enterprises.